Using Complex Conjugated Magnitudes- and Orthogonal Park/Clarke Transformation Methods of DC/AC/AC Frequency Converter - Dobrucky, B.; Benova, M.; Spanik, P. (Elektronika ir Elektrotechnika, 2009)
The paper deals with mathematical modeling of two-stage frequency converter system with induction motor. There are used two special methods of investigation: method of complex conjugated amplitudes, and the orthogonal Park/Clarke transformation method. The first one is used for steady-state investigation; the second one is suitable for investigation of three-phase electric circuits. The combination of both methods is very useful for analysis of three-phase electric motors in steady-state condition: constant angular speed, and when operator d/dt in its dynamical model is substituted by operator j, ν, ω, t. Then the effect of individual harmonic components on motor properties can be investigated. Ill. 9, bibl. 10 (in English; summaries in English, Russian and Lithuanian).